Factors influencing treatment decision‐making for cancer patients in low‐ and middle‐income countries: A scoping review - Marta Salek; Allison Silverstein; Alyssa Tilly; Pascale Yola Gassant; Sanjeeva Gunasekera; Diriba Fufa Hordofa; Donna Hesson; Caitlyn Duffy; Nauman Malik; Michael McNeil; Lisa M. Force; Nickhill Bhakta; et al. (Cancer Medicine, 2023)
Abstract Purpose In this scoping review, we evaluated existing literature related to factors influencing treatment decision‐making for patients diagnosed with cancer in low‐ and middle‐income countries, noting factors that influence decisions to pursue treatment with curative versus non‐curative intent. We identified an existing framework for adult cancer developed in a high‐income country (HIC) context and described similar and novel factors relevant to low‐and middle‐income country settings. Methods We used scoping review methodology to identify and synthesize existing literature on factors influencing decision‐making for pediatric and adult cancer in these settings. Articles were identified through an advanced Boolean search across six databases, inclusive of all article types from inception through July 2022. Results Seventy‐nine articles were identified from 22 countries across six regions, primarily reporting the experiences of lower‐middle and upper‐middle‐income countries. Included articles largely represented original research (54%), adult cancer populations (61%), and studied patients as the targeted population (51%). More than a quarter of articles focused exclusively on breast cancer (28%). Approximately 30% described factors that influenced decisions to choose between therapies with curative versus non‐curative intent. Of 56 reported factors, 22 novel factors were identified. Socioeconomic status, reimbursement policies/cost of treatment, and treatment and supportive care were the most commonly described factors. Conclusions This scoping review expanded upon previously described factors that influence cancer treatment decision‐making in HICs, broadening knowledge to include perspectives of low‐ and middle‐income countries. While global commonalities exist, certain variables influence treatment choices differently or uniquely in different settings. Treatment regimens should further be tailored to local environments with consideration of contextual factors and accessible resources that often impact decision‐making.